Education as State Control on Second Space: Sharia Regulation and Millennial Desire on Urban Cafes in Contemporary Bireuen City, Aceh: Sharia Regulation and Millennial Desire on Urban Cafes in Contemporary Bireuen City, Aceh - Mulyadi Mulyadi; Miswari Miswari (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2024)
This article aims to analyze the efforts to dominate thirdspace in urban millennial cafes in Bireuen City, Aceh, by state sharia. Thirdspace is a concrete space as the actuality of contestation in secondspace by each group. Because secondspace determines the domination of thirdspace, state sharia through authoritative institutions, namely Satuan Polisi Pamong Praja (Civil Service Police Unit) & Wilayatul Hisbah (Satpol PP&WH) is trying to take preventive action. This qualitative research uses an anthropological approach. Researchers collected data from observation, in-depth interviews, and literature studies related to research subjects. The theory used in this research is Thirdspace by Edward Soja about the process of forming thirdspace as a public place. The focus of this research is Bireuen City, as a strategic city from the point of view of rapid social change, advanced economy, strategic geographical location, and rapid development of public places for millennials. The research findings show that state sharia through Satpol PP&WH conducts Islamic religious education, especially theology and Islamic ethical philosophy education for millennials by visiting many high schools, as an effort to dominate thirdspace through secondspace, especially urban millennial cafes in Bireuen City.